Keadilan Dalam Bisnis Gadai - Sampe, Naomi (Sekolah Tinggi Agama Kristen Negeri Toraja, 2018)
The habit of debit and credit has become tradition in human culture as far back as. The system of debit and credit also happened in outgrowth. In hundreds years, it expand from barter system in primitive society towards variety methods, until now. There are many ways for people to get loans, and morover in easier manner. The commonly way in taking the allowance is by using bailed out. Thats why,nowdays there so many institution or person pop out to offer a term loan, such as bank, cooperative (enterprise) that emerge in saving and loan, credit union, financing instituion, loan office, and even moneylender. This research is needed to help emerge any understanding into some problem solving on how the christian ethics addressing the alternatives to face this problem of pawning.AbstrakBudaya utang piutang telah menjadi tradisi dalam masyarakat sejak dahulu. Sistem transaksi utang piutang juga mengalami perkembangan. Dari sistem barter dalam masyarakat primitif sederhana, berkembang melalui ratusan tahun menjadi berbagai macam cara hingga saat ini. Cara-cara yang dapat ditempuh untuk mendapatkan pinjaman saat ini beragam dan semakin mudah metodenya. Yang paling umum dilakukan adalah mengambil kredit dengan memberikan jaminan. Lantas, bermunculanlah berbagai lembaga/orang yang dapat memberikan pinjaman dengan bunga yang disepakati, seperti bank, koperasi simpan pinjam, credit union, lembaga finance dan pegadaian bahkan rentenir dengan resiko masing-masing. Masalah ini memerlukan kajian penelitian untuk memberi pandangan etis kristiani sebagai salah satu alternatif teologi menghadapi persolan bisnis gadai ini.